PERANCANGAN SMART SEATBELT SEBAGAI PERANGKAT PASSIVE SAFETY PADA KENDARAAN ANGKUTAN BARANG - Budi, Sigit Setijo; Dwifa`, M. Beny; Makhrojan, Agus (FSTPT Indonesia, 2015)
Seatbelt is a passive safety equipment that has become mandatory equipment in a motor vehicle in accordance with the mandate of the law. Seatbelt main function is to protect the driver and passenger from impact in the event of an accident. However, there is still reluctance from the driver to use this device. This study aims to overcome the reluctance of the driver in use seatbelt when driving. The research process is done by making smart seatbelt to be activated if the driver does not use a seatbelt. The results of this study are a smart seatbelt control system on the vehicle so that the system does not turn on when the seatbelt is not used used.